Knowledge of symptoms, social support, and parenting stress in fathers of children with ASD: implications for improved affective well-being - Mangen, Kathryn, author; Hepburn, Susan, advisor; Luong, Gloria, committee member; Lane, Shelly, committee member (Colorado State University. Libraries, 2021)
Parents of a child with Autism Spectrum Disorder (ASD) will likely experience a more challenging and stressful parenting experience than the average parent (Hayes & Watson, 2013). Previous literature has demonstrated that parenting a child with ASD can be highly stressful for mothers, yet there is scant literature on the experiences of fathers. With such little information, it is unclear what contributes to promoting fathers' affective well-being when caring for a child with ASD. The present study examines the associations between knowledge of ASD symptoms, perceived social support, parenting stress, and both positive and negative affect of fathers of a child with ASD within the context of the ABC-X model. Additionally, this study explores which variables predict fathers' positive affect and negative affect. Fifty-two fathers of individuals with ASD completed a battery of confidential online surveys measuring parenting stress, social support, knowledge of ASD symptoms, and positive/negative affect. Correlational analyses and regression analyses were conducted. Results suggest that fathers experience high levels of parental stress, and this parental stress is associated with overall affective well-being. Perceived social support is associated with negative affect and knowledge of ASD symptoms was found to not be associated with any of our variables. Limitations, implications for clinical interventions, and future directions are explored.
Keywords: autism spectrum disorder; parental stress; fathers; affective well-being